Affordable and Effective Microelectronic Engineering Teaching Package for Undergraduate Programme - Uda, Hashim, Prof. Dr.; Zul Azhar, Zahid Jamal, Prof. Dr.; Nur Hamidah, Abdul Halim; Mohammad Nuzaihan, Md Nor (International Exhibition of Inventions, 2010)
Prof. Dr. Uda Hashim and his team won silver at International Exhibition of Invention of Geneva 2006, 5th - 9th April 2006 was held at Palexpo, Geneva, Switzerland.